Probing neutrino oscillations in supersymmetric models at the Large Hadron Collider - de Campos, F. [UNESP]; Eboli, O. J. P.; Hirsch, M.; Magro, M. B.; Porod, W.; Restrepo, D.; Valle, J. W. F. (Amer Physical Soc, 2010)
The lightest supersymmetric particle may decay with branching ratios that correlate with neutrino oscillation parameters. In this case the CERN Large Hadron Collider (LHC) has the potential to probe the atmospheric neutrino mixing angle with sensitivity competitive to its low-energy determination by underground experiments. Under realistic detection assumptions, we identify the necessary conditions for the experiments at CERN's LHC to probe the simplest scenario for neutrino masses induced by minimal supergravity with bilinear R parity violation.